Appendix 4.10: Marcos Diary Entry, 25 September 1972 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
Arrests continue after the declaration of martial law, as do bureacratic shake-ups; Marcos here says that he has “dismissed some judges and punished some fiscals.” In the consulta with two justices, Fred Ruiz Castro asked, “Is this a coup [d’etat]?” Probably he was referring to a self-coup or autogolpe, which had happened many times throughout history. Marcos never referred to his means of assuming dictatorial powers as such, probably because to do so would be admitting that he violated the law.